2013
DOI: 10.1038/lsa.2013.72
|View full text |Cite
|
Sign up to set email alerts
|

High-aspect 3D two-photon polymerization structuring with widened objective working range (WOW-2PP)

Abstract: We developed a novel two-photon polymerization (2PP) configuration for fabrication of high-aspect three-dimensional (3D) structures, with an overall height larger than working distance of the microscope objective used for laser beam focusing into a photosensitive material. This method is based on a modified optical 2PP setup, where a microscope objective (1003 high N.A.), immersion oil and cover glass can be moved together into the photosensitive material, resulting in an effective higher and wider objective w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 24 publications
0
92
0
Order By: Relevance
“…at an angle to the axis of the structuring beam. Here, the change in refractive index induced to the photosensitive material by the polymerization process enables visualization of the polymerized structure [82]. Measuring this change in refractive index by interferometry was also proven feasible to be used for insitu monitoring of the polymer conversion [110].…”
Section: Pp Monitoringmentioning
confidence: 98%
See 2 more Smart Citations
“…at an angle to the axis of the structuring beam. Here, the change in refractive index induced to the photosensitive material by the polymerization process enables visualization of the polymerized structure [82]. Measuring this change in refractive index by interferometry was also proven feasible to be used for insitu monitoring of the polymer conversion [110].…”
Section: Pp Monitoringmentioning
confidence: 98%
“…3D structures with a height of 7 mm are demonstrated (see Fig. 20), which could hardly be built with the conventional 2PP set-up due to refractive index mismatch and laser beam disturbances [82]. The two-photon polymerization process consists of several physical phenomena such as generation and propagation of spatial and temporal intensity distribution, nonlinear two-photon absorption, bulk heating, reaction kinetics during polymerization and material dependent post-processing.…”
Section: Pp Process and Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…mm-nm scales), they are excellent candidates to be applied for the fabrication of three-dimensional (3D) microsized objects with high precision. 2,4 For instance, as demonstrated in Figure 6.5, using a laser with a wavelength of 780 nm and a pulse width of less than 140 fs, the fabrication of high aspect ratio (HAR) 3D microstructures such as a grid tower (grid width B771 nm and tower height B459 mm) and Tokyo Skytree (feature width B1.2 mm and height B293 nm) were made of photosensitive material by Obata et al 25 This recent work of microfabrication demonstrated here is promising for future applications. In addition, more various micro-to nanoscale technologies related with photosensitive materials have been currently explored and developed.…”
Section: Miniaturization Of Objectsmentioning
confidence: 99%
“…Inducing a two-photon absorption by femtosecond (fs) laser pulses, the polymerization within the volume of the resin with the formation of 3D structures occurs, the process being thus labeled as the two-photon polymerization (2PP). [32,33] In fact, the 2PP represents a rapid prototyping technology and according to Waterman et al, this type of technology may reduce the time to market by 90% and costs by up to 70%. [34] Owing to the versatility of the process, the 2PP technique was useful in the fields of photonics, [35] microfluidics, [36] and biological tissue engineering.…”
Section: Synthesismentioning
confidence: 99%